The Examination on Students‘ Parasocial Interaction and Brand Preference to Use Video Application in New Developing Area of Chengdu, China - Yan, Siyi (Scholar: Human Sciences, 2025)
Purpose: This research investigates the influences on university students’ parasocial interaction and brand preference regarding video applications in Chengdu, China. Seven variables were identified for examination, encompassing parasocial interaction, entertainment motive, perceived interactivity, self-disclosure, task attraction, physical attraction, and brand preference, with six hypotheses proposed to explore their interrelationships. Research Design, Data, and Methodology: A quantitative approach was employed in this study through the distribution of a questionnaire. The survey encompassed 500 students from two universities in Chengdu’s New Developing Area, known for their active usage of the Bilibili application. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were utilized as the analytical methods to assess goodness of fit and confirm the hypotheses proposed in the study. Results: Perceived interactivity, self-disclosure, and task attraction significantly contribute to parasocial interaction, which subsequently influences brand preference. However, the impact of entertainment motive on parasocial interaction was not supported. Furthermore, there is no support on the impact of physical attraction and parasocial interaction. Conclusions: These results underscore the importance of considering contextual factors such as geographical location. Furthermore, they provide valuable insights for content creators, video platform developers, and marketers seeking to effectively engage with and target this demographic in Chengdu, China.